Stable isotope variations of precipitation and streamflow reveal the young water fraction of a permafrost watershed - Song, Chunlin; Wang, Genxu; Liu, Guangsheng; Mao, Tianxu; Sun, Xiangyang; Chen, Xiaopeng (Hydrological Processes, 2017)
The streamflow age is an essential descriptor of catchment functioning that controls runoff generation, biogeochemical cycling, and contaminant transport. The young water fraction (F yw ) of streamflow, which can be accurately estimated with tracer data, is effective at characterizing the water age proportions of heterogeneous catchments. However, the F yw values of permafrost catchments are not known. We selected a watershed in the permafrost region of the Qinghai-Tibet Plateau (QTP) as our study area. Daily interval stable isotopes (deuterium and oxygen-18) of precipitation and streamflow were studied during the 2009 thawing season. The results show that the stable isotope compositions of precipitation and stream water have significant spatial and temporal variations. HYSPLIT backwards trajectory results demonstrate that the moisture in the study area mainly derived from the westerlies and southern monsoons. Thawing processes in the active layer of the permafrost significantly altered the stable isotope compositions of the stream water. The soil temperature, soil moisture, and air temperature are the main drivers of the stable isotope variations in the stream water. We estimated the young water fractions of the five catchments in the study area, which were the first estimates of the F yw in permafrost catchments in the QTP. The results show that an average of 15% of the streamflow is younger than 43days. Additional analyses show that the vegetation cover significantly controls the young water fraction of the streamflow. These results will improve our understanding of permafrost hydrological processes and water resource utilization and protection. The streamflow age is an essential descriptor of catchment functioning that controls runoff generation, biogeochemical cycling, and contaminant transport. The young water fraction (Fyw) of streamflow, which can be accurately estimated with tracer data, is effective at characterizing the water age proportions of heterogeneous catchments. However, the Fyw values of ...